ANALISIS PENYERAPAN TENAGA KERJA TERHADAP TRANSPORTASI ONLINE GRAB DI KOTA PAREPARE - Darmawan, Darmawan; Suhardi, Dayu; Jufri, Zulkifli (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The development of technology forced to change, the last decade people began to familiarize themselves with the increasingly massive development of technology. The purpose of this study is to find out the level of labor absorption to the existence of application-based online transportation (Grab) in the city of Parepare. The data collection techniques used are observations and interviews and then data analysis techniques are used, namely qualitative descriptive analysis. The results showed that the presence of app-based online transportation in The City of Parepare in this case Grab Indonesia has had a good impact on the people of Parepare City. The presence of Grab Indonesia provides new employment opportunities for people who do not have jobs or people who need side jobs for additional income. Grab's presence also contributes to improving the welfare of the community because with Grab people can earn additional income by working side by side as Grab Parepare driver partners.